2016
DOI: 10.3329/icpj.v5i10.29522
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of hypertension among business class community of Lahore, Pakistan

Abstract: Hypertension is one of the leading health issue in developing countries. There are many factors associated with hypertension like obesity, excessive intake of salt, smoking and drinking alcohol. Current study aims to assess the prevalence and determinants of hypertension among business class community in Lahore. A community based survey in Lahore was conducted to evaluate the prevalence and determinants in business class community aged 20- 45 year. Questionnaire was designed, translated into local language and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These findings align with research by Kamran et al, which highlighted the association between high salt intake and increased blood pressure in rural hypertensive patients in Pakistan (20). Furthermore, the study observed that a significant proportion of participants were not adhering to prescribed antihypertensive medications, a factor that critically affects blood pressure control and management (21).…”
Section: Discussionsupporting
confidence: 89%

Prevalence of Hypertension in People Aged 40 Years and Above

Muhammad Usama Maooz Awan,
Zaman Akram,
Hafiza Hamna Mushtaq
et al. 2024
JHRR
“…These findings align with research by Kamran et al, which highlighted the association between high salt intake and increased blood pressure in rural hypertensive patients in Pakistan (20). Furthermore, the study observed that a significant proportion of participants were not adhering to prescribed antihypertensive medications, a factor that critically affects blood pressure control and management (21).…”
Section: Discussionsupporting
confidence: 89%

Prevalence of Hypertension in People Aged 40 Years and Above

Muhammad Usama Maooz Awan,
Zaman Akram,
Hafiza Hamna Mushtaq
et al. 2024
JHRR
“…The participants’ ages ranged from 5–80 years, and the study populations included medical students, university teachers, in-service/retired adults, businessmen, drivers/conductors, factory workers, clerks, shopkeepers, all working individuals, elderly individuals, and school children. Six studies were conducted in rural areas [ 37 – 42 ], 8 were carried out in urban populations [ 43 50 ], and the remaining 23 (62.2%) sampled a combination of the two. Five (13.5%) studies included only women [ 37 , 51 – 54 ], 1 study [ 36 ] included only men, and 2 [ 48 , 50 ] were based on schoolchildren.…”
Section: Resultsmentioning
confidence: 99%
“…Seven (18.9%) studies (5 cross-sectional [ 40 , 41 , 57 , 61 , 66 ] and 2 case-control [ 31 , 36 ]) reported adjusted ORs (95% CI) using multiple logistic regression analyses. Six (16.2%) studies (cross- sectional [ 38 , 43 , 46 , 55 , 58 , 64 ]) had descriptive analyses and the remaining 7 (18.9%) studies analyzed data using the Chi-Square test, t-test, or correlation analyses ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation